Liturgy: Local and Contextual or Controlled from Above? A Nordic Perspective: Liturgical Renewal and Development in the Evangelical Lutheran Church of Finland in the Past Three Decades - Hulmi, Sini (Studia liturgica, 2019)
Is the liturgy local and contextual and growing from below, or is it controlled from above? Does the liturgy belong to the people and to the congregation, and are they allowed to use it in their own way? Or is the liturgy the property of the Church, which gives strict orders for its use? Is it powerful men and women, meaning those people with authority, and the institutions (for example, the Church Synod and the Bishops' Conference) who define the methods and ways in which liturgy is enculturated? Or do the ways of inculturation involve development from below, from the common people, even the poorest and most humble believers, at the congregational level? The balance between these two aspectstop-down and bottom-up worshiphas repeatedly shifted over the last three decades, and there have been tensions between them in the Evangelical Lutheran Church of Finland. The goal of this essay is to clarify the reason for this confusing situation related to authority, fixed orders and the creative development of liturgical life.